A)

Multiple Choice
Solve for p.
3(p + q) = p
(1 point)
q = –2/3 p
q = – 3/2p
p = –2/3 q
p = – 3/2q

1 answer

To solve for p, we want to isolate p on one side of the equation.

Starting with the equation 3(p + q) = p, let's distribute the 3 to both terms inside the parentheses:

3p + 3q = p

Now, let's subtract 3p from both sides to move all the p terms to one side of the equation:

3q = -2p

Finally, let's divide both sides by -2 to solve for p:

p = -3/2q

Therefore, the correct answer is p = -3/2q.